The Impact of a Computerized Clinical Decision Support Tool on Inappropriate Clostridium difficile Testing. (1st August 2017) - White, Duncan R.; Hamilton, Keith W.; Pegues, David A.; Hanish, Asaf; Umscheid, Craig A.
Abstract : OBJECTIVE: To evaluate the effectiveness of a computerized clinical decision support intervention aimed at reducing inappropriate Clostridium difficile testing DESIGN: Retrospective cohort study SETTING: University of Pennsylvania Health System, comprised of 3 large tertiary-care hospitals PATIENTS: All adult patients admitted over a 2-year period INTERVENTION: Providers were required to use an order set integrated into a commercial electronic health record to order C. difficile toxin testing. The order set identified patients who had received laxatives within the previous 36 hours and displayed a message asking providers to consider stopping laxatives and reassessing in 24 hours prior to ordering C. difficile testing. Providers had the option to continue or discontinue laxatives and to proceed with or forgo testing. The primary endpoint was the change in inappropriate C. difficile testing, as measured by the number of patients who had C. difficile testing ordered while receiving laxatives. RESULTS: Compared to the 1-year baseline period, the intervention resulted in a decrease in the proportion of inappropriate C. difficile testing (29.6% vs 27.3%; P =.02). The intervention was associated with an increase in the number of patients who had laxatives discontinued and did not undergo C. difficile testing (5.8% vs 46.4%; P <.01) and who had their laxatives discontinued and underwent testing (5.4% vs 35.2%; P <.01). We observed a nonsignificant increase in the proportion of patients with C. difficile related complications (5.0% vs 8.9%; P =.11). CONCLUSIONS: A C. difficile order set was successful in decreasing inappropriate C. difficile testing and improving the timely discontinuation of laxatives. Infect Control Hosp Epidemiol 2017;38:1204–1208